Category Shifts in the Translation of Dialogue: Reflecting Psychological Pressure in 'The Yellow Wallpaper’ from English to Indonesian - Nelli, Nelli; Kendenan, Esriaty Sega (JELITA, 2025)
This study explores how dialogue in “The Yellow Wallpaper” reflects the protagonist’s psychological distress and analyzes the category shifts in its translation from English to Indonesian. This study applies Catford’s (1965) translation shift theory, this study identifies structural, class, unit, and intra-system shifts in the Indonesian translation by Lystianingtyas Putri Alfani (2021). A descriptive qualitative method is used to classify these shifts and analyze their impact on the depiction of psychological distress in the translated text. The analysis is further supported by Hans Selye’s General Adaptation Syndrome (GAS) theory, which categorizes psychological distress into three stages: alarm, resistance, and exhaustion. The findings reveal that grammatical differences between English and Indonesian influence how the protagonist’s emotions are conveyed. Structural, class, unit, and intra-system shifts in translation play a role in preserving or altering the intensity of psychological distress. This study contributes to translation and literary studies by highlighting the challenges of translating emotional nuances and encouraging further reearch on translation strategies in literary texts that depict a character’s psychological condition.